Formation of Confidence and Sociability of Students in the First Three Years of Higher School Training - A R Akimova; M I Volk (Peoples' Friendship University of Russia (RUDN University), 2011)
The article is devoted to the study of confidence and sociability of students at different stages of social and psychological adaptation to higher school. The comparative analysis is carried out, the specifics of correlation and factor structures of confidence and sociability with indicators of adaptation in the first, second and third year students are disclosed.